COOPERATIVE MEMBERSHIP AND ENTREPRENEURIAL ORIENTATION OF WOMEN PALM-OIL SELLERS IN OGUN STATE, NIGERIA - Nurudeen Afolabi Sofoluwe; Toheebat Temitope Adelanwa; Olugbenga Chris Ologbon (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Women entrepreneurs in palm oil business face significant challenges associated with access to finance and formal institutional support leading to poor entrepreneurial outcomes. An increasing number of women have joined cooperative organizations to boost their entrepreneurial activities. However, the question of whether cooperative membership enables significant support for entrepreneurial success of the women remain unanswered. The study examined the cooperative role of women engaged in the palm oil business in their entrepreneurship drive and determined the factors responsible for entrepreneurship orientation among women and their levels. Primary data were collected using a structured questionnaire. The respondents were purposively sampled. Descriptive statistics and a multiple regression model were used to analyze the data. The results showed that cooperative membership has a significant influence on entrepreneurship drive among palm oil sellers. Additionally, financial support has a significant influence on the entrepreneurship traits of the women palm oil traders. The findings also indicate that the orientation of women toward risk-taking and business aggressiveness is high. Women entrepreneurs should be encouraged to increase their entrepreneurial aggressiveness and supported financially to sustain their palm oil business. Women palm oil sellers who are not members of co-operative societies should endeavor to join one to have access to low-cost financing to undertake entrepreneurship activities.